Antusiasme Netizen Indonesia Sebagai Endorsement Alami PSSI Dalam Menarik Minat Pemain Naturalisasi Bergabung Dalam Timnas Indonesia - Agustian, Fitrah; Sikki, Nurhaeni; Ilham, Muhammad; Sulistiana, Risa; Missa, Rony Rikus; Rizki, Andi Aulya; Ariyani, Alisiah Rezky (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This study aims to analyze the naturalization policy of football players in the Indonesian National Team, especially in the era of Shin Tae-yong's coaching. Through literature studies and media analysis, this study will examine the impact of the naturalization policy on improving the quality of the Indonesian National Team, internal team dynamics, potential conflicts that arise, and the influence of the enthusiasm of Indonesian netizens who act as natural endorsements for PSSI in attracting the interest of naturalized players to join the Indonesian National Team, in other words that these Indonesian netizens become natural digital marketing for PSSI to attract the interest of talented Indonesian diaspora players abroad to join the Indonesian National Team. This study concludes that the enthusiasm of netizens is a valuable asset for PSSI in an effort to strengthen the Indonesian National Team. In addition, this study will also provide recommendations for improving the naturalization policy so that it can be more optimal in improving the achievements of the Indonesian National Team.